2005
DOI: 10.3758/bf03193526
|View full text |Cite
|
Sign up to set email alerts
|

Sweep-induced acceleration in loudness change and the “bias for rising intensities”

Abstract: A pure tone changing continuously in intensity shows sweep-induced fading (SIF) of loudness as intensity sweeps down and may show a lesser degree of sweep-induced enhancement (SIE) as intensity sweeps up (Canévet & Scharf, 1990); the former effect has been called decruitment, the latter upcruitment. An opposite effect-upsweeps being judged to show more loudness change than downsweeps-has been reported by Neuhoff (1998). These disparate results might stem from several procedural differences. We found that diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 11 publications
7
64
0
Order By: Relevance
“…In these studies direct ratings were used, i.e., the loudness change reported was a single judgment. The overestimation for upramps has been found to be strongly dependent on end level of the ramp rather than on ramp size (Teghtsoonian et al, 2005). On the other hand, no loudness change overestimation for upramp sounds was found (Canévet et al, 2003;Susini et al, 2007), but a strong effect of ramp size was observed-as it could have been expected when measuring loudness change (Canévet et al, 2003).…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…In these studies direct ratings were used, i.e., the loudness change reported was a single judgment. The overestimation for upramps has been found to be strongly dependent on end level of the ramp rather than on ramp size (Teghtsoonian et al, 2005). On the other hand, no loudness change overestimation for upramp sounds was found (Canévet et al, 2003;Susini et al, 2007), but a strong effect of ramp size was observed-as it could have been expected when measuring loudness change (Canévet et al, 2003).…”
Section: Introductionmentioning
confidence: 78%
“…The synthetic vowel sound was based on Klatt's (1980) algorithm with a fundamental frequency of 100 Hz and three formant frequencies (450, 1450 and 2450 Hz) as in Neuhoff's (1998) study. In order to compare our results with those from previous studies (Neuhoff, 1998;Teghtsoonian et al, 2005), similar configurations of the control parameters were chosen.…”
Section: Stimulimentioning
confidence: 85%
See 3 more Smart Citations